THE SHARK FIN PATTERN AS A PREDICTOR OF SUDDEN CARDIAC DEATH IN ISCHEMIC AND NON-ISCHEMIC PATIENTS - Moza Guyanto; Fredy Tandri; Alexander Edo Tondas (Universitas Indo Global Mandiri, 2025)
Background: The “shark fin” pattern, also known as a triangular QRS–ST–T waveform, is a distinctive electrocardiographic (ECG) manifestation of ST-segment elevation myocardial infarction (STEMI). It is characterized by a triangular morphology resulting from the fusion of the QRS complex, ST segment, and T wave.Case Illustration: We present a case series of three patients exhibiting the “shark fin” ECG pattern. Two patients were adults with a history of ischemic heart disease, while one was a 19-year-old male with no significant past medical history. One adult patient was treated with thrombolytic therapy, and the other underwent percutaneous coronary intervention. One of the adult patients and the young patient developed malignant arrhythmias and subsequently experienced sudden cardiac death.Conclusion: The “shark fin” ECG pattern is associated with a poor in-hospital prognosis, including an increased risk of ventricular fibrillation (VF) and sudden cardiac death (SCD) in both ischemic and non-ischemic patients. When this pattern is identified, prompt and aggressive management is essential to improve patient survival.